2009
DOI: 10.1007/s12640-009-9075-4
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with Ethyl Pyruvate and Aspirin Enhances Neuroprotection in the Postischemic Brain

Abstract: Ethyl pyruvate (EP), a simple aliphatic ester of pyruvic acid, has been shown to act as an anti-inflammatory molecule in various pathological conditions, which include sepsis or hemorrhagic shock. Recently, we showed that ethyl pyruvate has a neuroprotective effect in the postischemic brain and also in KA-induced pathogenesis in the brain. In this study, we examined whether aspirin augments neuroprotective effect of ethyl pyruvate in transient focal ischemia model by complementing the neuroprotective effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
5
23
1
Order By: Relevance
“…In our previous report, we showed that combination treatment with ethyl pyruvate and aspirin enhances neuroprotection in the postischemic brain (Kim et al, 2010). Here, we confirmed the complementary effects of pyruvate and salicylic acid, the metabolic products of ethyl pyruvate and aspirin, respectively.…”
Section: Synergistic Neuroprotective Effects Of Pyruvate and Salicylisupporting
confidence: 82%
See 2 more Smart Citations
“…In our previous report, we showed that combination treatment with ethyl pyruvate and aspirin enhances neuroprotection in the postischemic brain (Kim et al, 2010). Here, we confirmed the complementary effects of pyruvate and salicylic acid, the metabolic products of ethyl pyruvate and aspirin, respectively.…”
Section: Synergistic Neuroprotective Effects Of Pyruvate and Salicylisupporting
confidence: 82%
“…It is beneficial for stroke patients in part due to its antiplatelet effect (Antithrombotic Trialists' Collaboration, 2002). In addition, aspirin also has anti-inflammatory (Pillinger et al, 1998;Feldman et al, 2001) and antiexcitotoxic effects (De Cristóbal et al, 2001;Castillo et al, 2003), which seem to complement the neuroprotective effects of ethyl pyruvate (Kim et al, 2010). In view of the multifactorial nature of cerebral ischemia, a multimechanism-based approach to drug development might be needed to maximize the efficacy of the drug treatment.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primer sequences of rat inducible NO synthase (iNOS) was described previously. 25) Immunoblotting BV2 cells were washed twice with cold phosphate buffered saline (PBS) and lysed in RIPA buffer (50 mM Tris-HCl, pH 7.4, 1% NP-40, 0.25% sodiumdeoxycholate, 150 mM NaCl, 1 mM Na 3 VO 4 , and 1 complete Mini protease inhibitor cocktail tablet (Roche Diagnostics, Switzerland)). The lysate was centrifuged for 15 min at 12000 rpm at 4°C and supernatants were loaded onto 6% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: )mentioning
confidence: 99%
“…The antigenantibody complex was detected by BM Chemiluminescence Blotting Substrate (Roche, Germany) using donkey antirabbit horseradish peroxidase-conjugated secondary antibody (Santa Cruz Biotechnology, U.S.A.). 25) …”
Section: )mentioning
confidence: 99%